Correlation of thyroid hormone profile and acute physiology and chronic health evaluation II (APACHE II) score with the survival in sepsis in a tertiary care centre - Aroor, Akshatha Rao; Bhat, Archana; Roshan, Maroli (Asian Journal of Medical Sciences, 2021)
Background: Thyroid hormone plays a pivotal role in the adaptation of metabolic function to stress and critical illness like sepsis. Thyroid dysfunction is associated with increased mortality in sepsis. The role of thyroid dysfunction as a prognostic marker in sepsis remains unclear. Aims and Objectives: To correlate the baseline thyroid function tests with APACHE II score and mortality in adult patients admitted with sepsis in Intensive Care Unit (ICU). Materials and Methods: This was a cross sectional, observational study done for a period of one year from September 2019 to September 2020 in a tertiary care referral hospital. Patients admitted with sepsis to ICU were scored on admission using APACHE II score. Blood was sent for thyroid function tests on admission. Patients were divided into survivors and non-survivors based on the outcome. Statistical analysis was done by calculating mean values, Fisher’s exact test and Pearson’s correlation. Results: A total of 52 patients were included. The mean age was 55.65± 18.55 years with a male predominance (M: F=1.4:1). Pneumonia was the commonest cause of sepsis in the study (20 patients,38.5%). Mortality was seen in 20 patients (38.5%) The mean values of thyroid hormones were lower in non-survivors. APACHE II Score was higher among the non-survivors as compared to survivors. (21.7±5.571 vs 19.78 ± 5.939, p value>0.05). Thyroid hormones (T3, T4, FT3, FT4) had a negative correlation with APACHE II score in non-survivors. TSH had significant positive correlation with APACHE II score in non-survivors (p value=0.027). Conclusion: Thyroid hormone levels did not correlate significantly with APACHE II score and mortality among the non-survivors of sepsis.